Proceedings of the Annual Symposium on Computer-Human Interaction in Play 2020
DOI: 10.1145/3410404.3414224
|View full text |Cite
|
Sign up to set email alerts
|

A Grounded Analysis of Player-Described Board Game Immersion

Abstract: Substantial research has explored the experience of immersion in digital games, but it is unclear whether this phenomenon extends to other game genres such as board games. Immersion is a concept widely discussed in the board game community by both developers and players and yet there is relatively little research in the area. This paper presents a grounded theory analysis of board game players' online discussions of immersion. This data is augmented by interviews with five board game players describing their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…Whilst the above categorisation and thematic classifcation of board games have been driven mostly by game designers and by surveys of games and their characteristics, in our previous study describing board game players' experiences of immersion [23] we found that theme-or world-building-can be a contributing factor to immersion. They classify board game players' experiences of immersion as way-points on a spectrum between "challenge" and "world-building", and defne immersion as a collection of experiences with the player at the centre of the experience, where the experience happens when a player's requirements are met by what is provided by the game and the surrounding gameplay.…”
Section: Theme and World-building In Board Gamesmentioning
confidence: 89%
See 2 more Smart Citations
“…Whilst the above categorisation and thematic classifcation of board games have been driven mostly by game designers and by surveys of games and their characteristics, in our previous study describing board game players' experiences of immersion [23] we found that theme-or world-building-can be a contributing factor to immersion. They classify board game players' experiences of immersion as way-points on a spectrum between "challenge" and "world-building", and defne immersion as a collection of experiences with the player at the centre of the experience, where the experience happens when a player's requirements are met by what is provided by the game and the surrounding gameplay.…”
Section: Theme and World-building In Board Gamesmentioning
confidence: 89%
“…Whilst we have considered to focus on a soundtrack's ability to enhance immersion (a quality often advertised in board game marketing), our previous work into board game players' subjective experiences of immersion [23] found that players defne immersion in a variety of ways which makes measurement of the experience difcult. Further, certain characteristics of board games (i.e., lack of digital display) make it incompatible with standardised video game immersion questionnaires.…”
Section: Methodology 31 Aims: Measuring and Investigating Impact Of A...mentioning
confidence: 99%
See 1 more Smart Citation
“…We collected at least two answers from each type of NPP: speakers, elected officials, experts, teachers, and citizens. The grounded theory approach (Charmaz, 2014; Farkas et al, 2020) provided the method to organize and interpret the answers to the questionnaires. We compared all the answers, grouping them by ideas and concepts, in a gradual, hierarchic, and coded way.…”
Section: Data Collectionmentioning
confidence: 99%
“…War themed games such as 'Twilight Imperium', 'Star Wars: Rebellion' and 'Twilight Struggle'; adventure games involving characters following a quest such as 'Gloomhaven' and 'Nemesis'; card games such as '7 Wonders Duel and 'Wingspan'; party games in-cluding 'Codenames' and 'Secret Hitler'; and science fiction related games such as 'Terraforming Mars' and 'Scythe' are popular examples of only a few of the categories of modern board games. With the enhanced design choices that improve immersion, diversity and complexity of themes, there is an increase in engagement in board games as a hobby or a passion [3].…”
Section: Introductionmentioning
confidence: 99%